Alcohol Consumption and Risk of All-Cause and Cardiovascular Disease Mortality in Men. (20th July 2011) - Howie, Erin K.; Sui, Xuemei; Lee, Duck-chul; Hooker, Steven P.; Hébert, James R.; Blair, Steven N.
Abstract : This study examined the association between consumption of alcoholic beverages and all-cause and cardiovascular disease (CVD) mortality in a cohort of men (n = 31, 367). In the Cox proportional hazards model adjusted for age, year of examination, body mass index (BMI), smoking, family history of CVD, and aerobic fitness, there were no significant differences in risk of all-cause mortality across alcohol intake groups. Risk of CVD mortality was reduced 29% in quartile 1 (HR = 0.71, 95% confidence interval (CI): 0.53, 0.95) and 25% in quartile 2 (HR = 0.75, 95% CI: 0.58, 0.98). The amount of alcohol consumed to achieve this risk reduction was <6 drinks/week; less than the amount currently recommended. The addition of other potential confounders and effect modifiers including blood pressure, insulin sensitivity, lipid levels, and psychological variables did not affect the magnitude of association. Future research is needed to validate the current public health recommendations for alcohol consumption.